The Advances of Laparoscopic Gastrectomy for Gastric Cancer - Yeon-Ju Huh; Joo-Ho Lee (Gastroenterology Research and Practice)
Laparoscopic gastrectomy is evolving. With the increasing expertise and experience of oncologic surgeons in the minimally invasive surgery for gastric cancer, the indication for laparoscopic gastrectomy is expanding to advanced cases. Many studies have demonstrated the benefits of minimally invasive surgery, including reduced risk of surgery-related injury, reduced blood loss, less pain, and earlier recovery. In order to establish concrete evidence for the suitability of minimal invasive surgery for gastric cancer, many multicenter RCTs, comparing the short- and long-term outcomes of laparoscopic versus open surgery, are in progress. Advances in laparoscopic gastrectomy are moving toward increasingly minimally invasive approaches that enable the improvement of the quality of life of patients, without compromising on oncologic safety.